Wartości i praktyki wyróżniające organizacje wiedzy - Stańczyk, Sylwia (Values and practices distinguishing over knowledge enterprise, 2006)
The main purpose of this article is to show crucial values and practices from the Knowledge Enterprise point of view. The Knowledge Enterprise is the perspective of the enterprise which shows all knowledge-related activities, resources and issues. Generally known examples - in the meaning of international character and recognized, global brand-knowledge enterprise are used in this article. Its author assumed that specific values and organizational practices of international corporations determine their world wide development.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1132, s. 205-213